PENGARUH PENGORGANISASIAN DAN MOTIVASI KERJA SERTA KEMAMPUAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA BADAN PERPUSTAKAAN DAN ARSIP DAERAHKABUPATEN KUTAI TIMUR - Hayati Hayati; Prof. Dr. Hj. Syarifah Hudayah, M.Si; Dr. Michael, MS (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACT          This study is a research quantitive assosiatife, In the sense of research based on the exixtence of a causal relationship between two or more variables. Using primary and secondary data, while the object of this study are employees of Libraries and Archives area (Bapusipda) East Kutai Regency, with a total sample of 120 respondents.           The purpose of this research is to determine the influence of the organization and  motivation and ability of employes working on the performance of employes in Libraries and Archives  area Body East Kutai Regency.           Analytical testing of hypotheses,  using SPSS 16.0. Response of this research are employees of Libraries and Archives area East Kutai Regency with a simple size of 120 respondents. The analysis showed that: The organization and the motivation and ability of employees positive effect on work performance of employes in Libraries and Archives Body East Regency.